Chronicity of Uncorrected Hyponatremia and Clinical Outcomes in Older Patients Undergoing Hip Fracture Repair - Ayus, Juan Carlos; Fuentes, Nora; Go, Alan S.; Achinger, Steven G.; Moritz, Michael L.; Nigwekar, Sagar U.; Waikar, Sushrut S.; Negri, Armando Luis (Frontiers in Medicine, 2020)
Background: Mild chronic hyponatremia is a risk factor for hip fracture but remains uncorrected in most patients. We addressed whether pre-operative chronicity of uncorrected hyponatremia influences outcomes after hip fracture repair. Materials and Methods: In this cohort study we identified elderly adults hospitalized for hip fracture repair between 2007- 2012 with plasma sodium measured at admission and ≥1 pre-admission outpatient measurement. Patients were classified as being normonatremic (NN, plasma sodium 135-145 mmol/L), chronic prolonged hyponatremia (CPH, ≥2 consecutive plasma sodium values <135 mmol/L over >90 days) or recent hyponatremia (one plasma sodium <135 mmol/L within 30 days before admission with previously normal plasma sodium). Length of hospital stay, in-hospital death, postoperative complications, 30-day readmission, and long-term mortality were the evaluated outcomes. Multivariable Cox regression was used to evaluate the association of hyponatremia status with outcomes. Results: Among 1571 eligible patients, 76.7% were NN, 14% had CPH, and 9.1% had RH. Compared with NN patients, CHN patients were older and more likely to have prior heart failure, alcoholism and anticonvulsant drug use. In multivariable analyses, neither CPH or RH were associated with hospital length of stay, in-hospital or 30-day death, or 30-day readmission, while RH was associated with post-operative sepsis (adjusted odds ratio [aOR] 1.84, 95%, CI:1.01-3.35). Only CPH was independently associated with long-term all-cause death (OR 1.53, 95%, CI:1.12-2.09). Conclusions: Mild hyponatremia affects nearly 1 in 4 patients undergoing hip fracture repair. Only Chronic prolonged hyponatremia was independently associated with excess long-term mortality. Future studies should evaluate if correction of hyponatremia could decrease long-term mortality after hip fracture repair.